Foundations of personal fitness : any body can-- be fit! - Rainey, Don; Murray, Tinker Dan, 1951- (New York : Glencoe , McGraw-Hill, 2005)
520 Discusses the foundations of physical fitness, the benefits of regular exercise, and the advantages of weight training and proper nutrition
pt.1 text -- pt.2 teacher's edition
Includes index
Keywords: Physical fitness -- Juvenile literature -- Health aspects; Exercise -- Juvenile literature -- Physiological aspects; Health -- Juvenile literature